The Role of Using Mobile Learning in Improving Graphic Design Skills of Practitioner Designers and Their Attitudes Towards it (The International Journal of Educational Sciences and Arts, 2024)
Mobile learning has emerged as a prominent trend in recent years, offering a valuable source of education and training for graphic designers. This study aimed to explore the impact of mobile learning on enhancing graphic design skills and assess the attitudes of practicing designers towards it. A descriptive survey method was employed, involving 534 conveniently selected practicing designers with familiarity in social media platforms. An electronic questionnaire was distributed via email and social media platforms in Saudi Arabia. Statistical analysis using SPSS software revealed a strong consensus among designers regarding the effectiveness of mobile learning in improving their design skills. Technical and printing skills were rated highly, while creativity and innovation were exceptionally high. The results of the research found a statistically significant differences at the level (≥ α 0,05) in improving graphic design skills according to gender, were high among males. Educational qualifications and specialization did not show any significant differences. However, variations were observed among different age groups and levels of experience. The study recommended further research in the field of learning and enhancing graphic design skills, along with the establishment of a dedicated educational platform for knowledge exchange and staying updated with the latest developments.
Keywords: Graphic Designers; Distance Learning; Creativity Skills; Technical Skills; Smart Devices